The modern approach to the treatment of diffuse - generalized forms of hypertrophic cardiomyopathy in the cardiac surgery - A. N. Shapieva; S. V. Fedulova; N. L. Cherepenina; V. S. Klimenko; D. G. Podoliak (Кубанский научный медицинский вестник, 2016)
To evaluate the results of surgical treatment of patients with diffuse-generalized form of hypertrophic cardiomyopathy by performing extended myectomy ventricular septal longitudinal parietal resection of the hypertrophied papillary muscles and universal mitral valve replacement. We have operated 18 patients (10 men and 8 women) with diffuse-generalized form of hypertrophic cardiomyopathy HCM. The average age of the patients was 48 ± 10,9 years. Hospital mortality was 0%. At 1 year after surgery according echocardiogram thickness of interventricular septum decreased from 1,9 ± 0,3 cm to 1,5 ± 0,2 cm, the pressure gradient in the left ventricular outflow tract decreased from 75,9 ± 5,6 mm. Hg up to 3,2 mm Hg ± 20.4, the size of the left atrium decreased from 4,5 ± 0,4 to 4,2 ± 0,3 cm. The functional class decreased from III to I-II NYHA. In the late postoperative period (2 years), 1 patient died. Conclusion: The results indicate that our proposed method of surgical treatment of diffuse - a generalized form of HCM is an effective procedure that gives good functional results.